HPLC-DAD-APCI/ESI-MSn analysis of carotenoids and α-tocopherol in Costa Rican Acrocomia aculeata fruits of varying maturity stages. (March 2018) - Schex, Roland; Lieb, Veronika M.; Jiménez, Víctor M.; Esquivel, Patricia; Schweiggert, Ralf M.; Carle, Reinhold; Steingass, Christof B.
Abstract: Carotenoids and tocopherols were characterised in the meso- and exocarp of wild-growing Costa Rican Acrocomia aculeata fruits. Comprehensive profiling of these lipophilic micronutrients in fruits of three varying maturity stages was conducted for the first time. A method for the simultaneous extraction and quantitation of carotenoids and α-tocopherol was developed and validated. Detailed HPLC-DAD-APCI/ESI-MS n analyses enabled the identification of α-tocopherol and 25 carotenoids. The latter comprised antheraxanthin, β-carotene, lutein, luteoxanthin, neoxanthin, phytoene, phytofluene, violaxanthin, zeaxanthin, and several ( Z )-isomers of the aforementioned compounds. Quantitation by HPLC-DAD/FLD revealed total carotenoid concentrations of 872 ± 178 and 3075 ± 407 μg/100 g fresh weight in the meso- and exocarp of fully ripe fruits, respectively. In both fruit fractions, progressing maturation resulted in the accumulation of phytoene, phytofluene, (all- E )-zeaxanthin, (all- E )-antheraxanthin, and (all- E )-violaxanthin. Carotenoid profiling was supported by multivariate data analysis. Carotenoid precursors and xanthophyll cycle pigments characterised Macauba fruits of full maturity. Graphical abstract: Highlights: Simultaneous extraction of carotenoids and α-tocopherol from Macauba fruits Identification of 25 carotenoids and α-tocopherol by HPLC-DAD-APCI/ESI-MS n Quantitation in the meso- and exocarp of three progressing maturity stages PCA was used for pattern recognition among the Macauba fruit samples.